MODEL MANAJEMEN PENGUATAN KARAKTER BERBASIS NILAI ISLAM MULTIKULTURAL MELALUI PARTISIPASI KELUARGA DAN KOMUNITAS DI SEKOLAH DASAR - Sismanto Sismanto; Sri Andriani; Luis Ignacio Silva Neira; Yusnia Binti Khalifah (MPI STAI Sangatta Kutai Timur, 2026)
This study aims to describe the management of character education grounded in multicultural Islamic values, analyze the implementation of character strengthening through family and community participation, and formulate a character-strengthening management model for SD YPPSB 3 Sangatta. The study employed a qualitative case study design. Research participants included foundation representatives, education directors, principals, vice principals, teachers, school committee members, parents, and students, selected purposively based on their involvement in the character strengthening program. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using data condensation, thematic categorization, data display, and conclusion drawing. The findings reveal that character strengthening was developed through three main dimensions: love, intellectuality, and leadership, which were integrated into the school culture, classroom learning, daily habits, and social activities. Character strengthening was reinforced through family and community involvement, including school-parent communication, parenting programs, social activities, and community collaboration. This study proposes a multicultural, Islamic values-based character strengthening management model that positions schools, families, and communities as an integrated ecosystem for character education. The theoretical contribution of this study lies in the development of a social-ecosystem-based character education management approach that is not solely centered on the formal curriculum but also on social relationships and students’ lived experiences within multicultural environments.